Pengaruh Diskon, Ongkir, dan Ontime Delivery Terhadap Keputusan Pembelian: Survei Konsumen Gofood di Jabodetabek - Muhammad Ahzami Amin; Aminah Nuriyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the influence of Discount, Shipping Cost, and Ontime Delivery on the Purchase Decision of GoFood consumers in the Jabodetabek area.The research adopts a descriptive quantitative approach involving 428 GoFood users. Data were collected through questionnaires and analyzed using SPSS with multiple linear regression tests, t-tests, F-tests, and the coefficient of determination (R²). Discount, Shipping Cost, and Ontime Delivery each have a positive and significant effect on purchase decisions. Simultaneously, the three variables also have a significant effect (F = 460.492), contributing 76.5% to purchase decisions, while the remaining 23.5% is influenced by other factors beyond this study. These findings indicate that the three variables are dominant factors influencing GoFood consumer purchase decisions in Jabodetabek.